Development of New Antimicrobial Oleanonic Acid Polyamine Conjugates - Elmira F. Khusnutdinova; Véronique Sinou; Denis A. Babkov; Oxana Kazakova; Jean Michel Brunel (MDPI AG, 2022)
A series of oleanolic acid derivatives holding oxo- or 3-N-polyamino-3-deoxy-substituents at C3 as well as carboxamide function at C17 with different long chain polyamines have been synthesized and evaluated for antimicrobial activities. Almost all series presented good to moderate activity against Gram-positive S. aureus, S. faecalis and B. cereus bacteria with minimum inhibitory concentration (MIC) values from 3.125 to 200 µg/mL. Moreover, compounds possess important antimicrobial activities against Gram-negative E. coli, P. aeruginosa, S. enterica, and EA289 bacteria with MICs ranging from 6.25 to 200 µg/mL. The testing of ability to restore antibiotic activity of doxycycline and erythromycin at a 2 µg/mL concentration in a synergistic assay showed that oleanonic acid conjugate with spermine spacered through propargylamide led to a moderate improvement in terms of antimicrobial activities of the different selected combinations against both P. aeruginosa and E. coli. The study of mechanism of action of the lead conjugate 2i presenting a N-methyl norspermidine moiety showed the effect of disruption of the outer bacterial membrane of P. aeruginosa PA01 cells. Computational ADMET profiling renders this compound as a suitable starting point for pharmacokinetic optimization. These results give confidence to the successful outcome of bioconjugation of polyamines and oleanane-type triterpenoids in the development of antimicrobial agents.